Care of the newborn by ten teachers - Lumsden, Hilary; Holmes, Debbie (London : Hodder Arnold, 2010)
'Care of the Newborn by Ten Teachers' presents a detailed account of care of the normal neonate - including the minor health problems that midwives are expected to deal with on a daily basis - providing care and treatment strategies for the neonate and family.
Keywords: Neonatology; Newborn infants; Newborn infants